A SYSTEMATIC LITERATURE REVIEW OF USING SONGS TECHNIQUE IN TEACHING EFL TERTIARY STUDENTS - Ete Rahmatia; Maulina Maulina; Muflihun Muflihun; Julianti Julianti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study analyzed content of 30 included previous published research articles from 2020 to 2024 focusing on how using songs can help improve EFL students’ pronunciation in tertiary education. Using different online tools like WhatsApp, Google Classroom, YouTube, Spotify, Joox, and TikTok to teach pronunciation through English songs, the results show that using songs in class played through those platforms helps EFL students improve important parts of pronunciation, such as sounds, stress, tone, rhythm, and how words connect when they speak. Besides, songs also help students copy native speakers, listen better, stay motivated, and feel less nervous when speaking. Among the tools studied, Spotify was used the most and worked best because it has features like matching lyrics and lets students learn on their own. This research gives teachers and language experts ideas on how to use songs and digital tools to make pronunciation lessons more effective for English learners.